THE EFFECT OF EMPOWERMENT, EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL COMMITMENT TOWARDS PERFORMANCE OF GOVERNMENTAL-EMPLOYEES OF FINANCIAL-MANAGEMENT - Liz Zeny Merry; Faroman Syarief (Program Studi S3 Ilmu Manajemen, 2017)
The objectives of this research is to study the influence of empowerment, employee engagement, and organizational commitment on performance of the financial management staffs at Riau Islands Provincial Government. Quantitative approach used in this research with survey method. The samples of this research were 230 staffs selected randomly. The data were obtained by distributing questionnaire and analyzed by using path analysis. The results of research shows that: (1) empowerment, employee engagement and organizational commitment had a positive direct effect on employee performance; (2) empowerment and employee engagement had a positive direct effect on organizational commitment; (3) empowerment have a positive direct effect on employee engagement. The research findings recommend to improve employee performance by improving empowerment, employee engagement and organizational commitment of the financial management staff at Riau Island Provincial GovernmentKeywords: empowerment, employee engagement, organizational commitment, and performanceRealizing